Microgels enable capacious uptake and controlled release of architecturally complex macromolecular species. (16th June 2017) - Walta, Stefan; Pergushov, Dmitry V.; Oppermann, Alex; Steinschulte, Alexander A.; Geisel, Karen; Sigolaeva, Larisa V.; Plamper, Felix A.; Wöll, Dominik; Richtering, Walter
Abstract: This study highlights the use of microgels as containers of high capacity for uptake and triggered release of multi-functional guests. As a model guest, heteroarm star-shaped copolymers (miktoarm stars) are chosen, as their certain arms could carry different active moieties, while other arms could act as "stickers" to the microgel host. Electrostatic attraction is used as a binding principle, wherein positively charged bis-hydrophilic miktoarm stars interact with negatively charged microgels. Functioning of microgels as containers with high capacity offers the possibility to construct promising stimuli-responsive uptake and release systems. Hence, aqueous mixtures of these oppositely charged polymeric components, the microgels and the miktoarm stars, were investigated in dependence on their initial charge ratio ( icr  = [cationic charges]/[anionic charges]) and on the concentration of a low molecular weight salt. The miktoarm stars are able to penetrate into the microgels to compensate their negatively charged groups. The amount of the miktoarm stars bound to the microgels can be controlled via ionic strength of the system, with limiting cases from quantitative binding to no binding. Then, such a microgel-based polyelectrolyte complex consists of one microgel and more than 1000 miktoarm stars. Furthermore, a jump-wise increase of ionic strength in solutions of the complexes triggers the complete release of the miktoarm stars from the microgel, and the system stays always colloidally stable. Thus, microgel-based polylectrolyte complexes provide opportunities for many important applications, especially in targeted/controlled delivery. Graphical abstract: Highlights: Ionic microgels enable capacious uptake of oppositely charged miktoarm stars. The amount of the miktoarm stars bound to the microgels is controlled by the salt concentration. A jump-like increase of the salt concentration triggers release of the miktoarm stars from the microgels. Modern fluorescence techniques allow for a quantification of uptake and release of labelled polymer species.